Customary Court Authority in Resolving Minor Violations: A National Legal Perspective - Shohib Muslim (Journal of Adat Recht, 2025)
This study analyzes the authority of customary courts in resolving minor violations within Indonesia’s national criminal law framework using a normative juridical approach. Findings show that customary courts apply restorative justice through reconciliation, apology rituals, and compensation based on community deliberation, resulting in higher conflict resolution effectiveness and reduced recidivism. However, the national legal system places customary authority in a subordinate position because customary settlements are considered valid only when aligned with state law and approved by law enforcement actors. This creates structural asymmetry where customary mechanisms are culturally successful but legally constrained. The study concludes that harmonization is necessary by granting customary courts primary jurisdiction over minor violations while ensuring procedural safeguards and supervisory oversight from state courts. Such integration would reduce courtroom congestion, strengthen access to justice, and preserve cultural identity within national criminal law development.